2011
DOI: 10.4103/0253-7613.75660
|View full text |Cite
|
Sign up to set email alerts
|

Effect of fruit extract of Fragaria vesca L. on experimentally induced inflammatory bowel disease in albino rats

Abstract: Aim:Ulcerative colitis and Crohn’s disease are chronic recurrent inflammatory bowel disease (IBD) of unknown origin. Oxidative stress is believed to be a key factor in the pathogenesis and perpetuation of the mucosal damage in IBD.Materials and Methods:Ethanolic extract of Fragaria vesca (EFFV) fruits was prepared by percolation method and subjected to oral toxicity testing using OECD guidelines. Albino rats were pretreated orally for 5 days with 3% gum acacia in control, EFFV 500 mg/kg in test and 5-aminosali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(22 citation statements)
references
References 17 publications
0
18
0
1
Order By: Relevance
“…In support of these observations and the role of ROS generation in TNBS colitis, Loguercio et al [29] reported that glutathione supplementation decreased oxidative damage in TNBS colitis. Similarly, Kanodia et al [30] recorded that fruit extract of Fragaria vesca exerts significant reduction in the levels of myeloperoxidase with concomitant increase in CAT and SOD in rat IBD models. Role of three different forms of Nitric Oxide Synthases (NOS), namely eNOS, iNOS and nNOS has been studied in TNBS and DDS induced colitis model [31].…”
Section: Discussionmentioning
confidence: 88%
“…In support of these observations and the role of ROS generation in TNBS colitis, Loguercio et al [29] reported that glutathione supplementation decreased oxidative damage in TNBS colitis. Similarly, Kanodia et al [30] recorded that fruit extract of Fragaria vesca exerts significant reduction in the levels of myeloperoxidase with concomitant increase in CAT and SOD in rat IBD models. Role of three different forms of Nitric Oxide Synthases (NOS), namely eNOS, iNOS and nNOS has been studied in TNBS and DDS induced colitis model [31].…”
Section: Discussionmentioning
confidence: 88%
“…Oxidative stress is believed to play a key role in the pathogenesis of IBD-related intestinal damage. As a matter of fact, intestinal mucosal damage in the IBD, including CD and UC, is related to both increased free radical production and to a low concentration of endogenous antioxidant defense [19].…”
Section: Discussionmentioning
confidence: 99%
“…One unit of MPO activity was defined as that degrading one micromole of peroxidise per minute at 25°C. This calculation was done by using following formula:[17]…”
Section: Methodsmentioning
confidence: 99%